Practice Guidelines for the Assessment of Clinically Significant Treatment Outcomes in the Children's Mental Health System. Issue 2 (3rd March 2016) - Chomycz, Suzanne; Schmidt, Fred
Abstract : The use of program evaluation to monitor client change and improve intervention effectiveness is gaining increasing importance in the mental health field. However, there is a lack of literature available in community-based clinics for those who desire to evaluate the effectiveness of services. Through this article the authors review the literature on the best methods to assess clinically significant treatment outcomes in community-based children's mental health services. The strengths and weaknesses of commonly recommended methods of evaluating change are discussed (i.e., reliable change index, percentage of improvement, normative comparisons, and effect size) using a dataset from a community-based parenting program ( N  = 308).